2014
DOI: 10.9788/tp2014.1-01
|View full text |Cite
|
Sign up to set email alerts
|

Relações familiares de adolescentes cumprindo medida socioeducativa restritiva de liberdade: uma revisão narrativa da literatura

Abstract: ResumoO objetivo deste artigo foi realizar uma revisão narrativa sobre a relação entre o sistema familiar e a conduta infracional de jovens. Foram consultadas as bases de dados SciELO; LILACS; BVS; PePSIC; PsycNET; APA PsycNET; Science Direct e Web of Knowledge (ISI). Resultaram da busca 19 artigos que atenderam aos critérios de inclusão. A análise dos artigos mostrou que alguns fatores familiares comumente encontram-se associados à condição de infrações à lei e ao cumprimento de medida sócio-educativa de inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…There are many factors that can contribute to adolescents being vulnerable and committing infractions, especially family structure, low socioeconomic status, living in the criminal environments, and cases of abandonment. 10 In this study, a low proportion reported attending school before entering the Educational Center, a fact that may reflect the failure of the government to maintain the fundamental right to inclusive and quality education. 5 It is also possible that these adolescents experience adaptation difficulties, considering that the school is not attractive and that they may not be able to live with the limits imposed in this environment.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…There are many factors that can contribute to adolescents being vulnerable and committing infractions, especially family structure, low socioeconomic status, living in the criminal environments, and cases of abandonment. 10 In this study, a low proportion reported attending school before entering the Educational Center, a fact that may reflect the failure of the government to maintain the fundamental right to inclusive and quality education. 5 It is also possible that these adolescents experience adaptation difficulties, considering that the school is not attractive and that they may not be able to live with the limits imposed in this environment.…”
Section: Discussionmentioning
confidence: 65%
“…It is not unified and often fails, and may cause the adolescent to be unable to identify what is right or wrong, increasing their chances of displaying aggressive, antisocial behaviors and initiating drug contact, leading to criminality. 10 The use of alcohol and drugs which is a very common occurrence in the population studied is another aggravating factor that greatly contributes to the increased vulnerability of adolescents. The use of psychoactive substances reduces the ability to discern risk, favoring greater exposure to vulnerable situations, and the possibility of sexual practice as a bargaining tool for drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos discorrem sobre a preocupação (25)(26) . Há estudos direcionados à importância da orientação da família, seu papel protetor ao uso de drogas pelos jovens, estimulando uma vida saudável e o cuidado mútuo (15) .…”
Section: Resultsunclassified
“…Onde predominam ideias de causalidade linear e determinismo psíquico ou biológico, a liberdade não é tratada como uma característica fundamental do ser humano. Já no âmbito dos estudos em Psicologia publicados sobre o tema, a liberdade é referida, frequentemente, em seu sentido jurídico de privação de liberdade, como pesquisas envolvendo pessoas encarceradas (Castro & Teodoro, 2014;Gomes & Conceição, 2014;Castro & Guareschi, 2008;Zappe, Santos, Ferrão & Dias, 2013;Marques & Ribeiro, 2013). Como May (1987) aponta, a liberdade sempre esteve historicamente significada como algo valioso, a ser conquistado e preservado, o que a coloca como um fenômeno separado e externo ao ser humano, além de imbuído de um valor unicamente positivo, já que é significada como a ausência de barreiras, limites ou prisões (Yalom, 1980).…”
Section: Introductionunclassified